VIRTUAL LABORATORY FOR VIRTUAL ANALYSIS IN TECHNICAL EDUCATION - Budi Raharjo; Yuli Fitriyanto; Sumaryanto Sumaryanto (Journal of Engineering, Electrical and Informatics, 2022)
Face-to-face technical instruction is subject to the existence of instrumentation and room. The fee, security, and listing can manner blockade to the administration directly in the laboratory. Virtual analysis can be adopted to increase the scholar's expertise by combining pre-laboratory for live analysis and serving approach to implementing that cannot be used securely personality. Virtual learning is applied in many areas, but questions are left over about how it should be used in engineering, this is an area that is mainly dependent on face-to-face laboratory and classroom settings. The purpose of this research is to adapt the common virtual laboratory idea to special demands, Virtual laboratories are not intended to change face-to-face discipline but to add to class time and offer a useful reserve as required. In addition, the experimental development method in this study was carried out by 3 virtual platforms: “Lab-VIEW”, “MAT-LAB”, and “Unity”. The 1st form of the Helicopter-machine Virtual Laboratory was advanced at Lab-VIEW. Virtual laboratories offer a semi-hands-on experience in college learning that might overlook physical learning. It means a type of active learning method to be adopted in university. The result of this research is a brief investigation of development possibilities in Unity. So that in the future, Unity exploration can be done further and in more detail. Scope This research consists of themes plated by Engineering Measurement Laboratory 1 learning. Engineering lectures might reflect these topics to carry out Virtual analysis in their laboratory and traditional classroom learning. The points that might advantage of the method consist of Mechanical Systems Laboratory, Energy Systems Laboratory, Thermodynamics, and Dynamics. It is hoped that this research will cocked the expansion of more Virtual analysis that increase engineering education in the future.